2022
DOI: 10.3390/en15144981
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient AnMBRs Technology for Treatment of Wastewaters: A Review

Abstract: In recent years, anaerobic membrane bioreactor (AnMBRs) technology, a combination of a biological reactor and a selective membrane process, has received increasing attention from both industrialists and researchers. Undoubtedly, this is due to the fact that AnMBRs demonstrate several unique advantages. Firstly, this paper addresses fundamentals of the AnMBRs technology and subsequently provides an overview of the current state-of-the art in the municipal and domestic wastewaters treatment by AnMBRs. Since the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 209 publications
(406 reference statements)
0
2
0
Order By: Relevance
“…Recently, Rahman et al [70] performed a review of the historical advancement in MBR technology toward sustainable wastewater management. Tomczak and Gryta [71] outlined energy-efficient anaerobic MBR (AnMBR) technology for WWT and demonstrated that AnMBRs have lower energy demand than typical WWTPs.…”
Section: Laboratory-scale Researchmentioning
confidence: 99%
“…Recently, Rahman et al [70] performed a review of the historical advancement in MBR technology toward sustainable wastewater management. Tomczak and Gryta [71] outlined energy-efficient anaerobic MBR (AnMBR) technology for WWT and demonstrated that AnMBRs have lower energy demand than typical WWTPs.…”
Section: Laboratory-scale Researchmentioning
confidence: 99%
“…Consequently, as was indicated in [47], the amount of biogas produced in AnMBRs is more significant than that obtained via conventional processes of the wastewater treatment. The undeniable advantages of AnMBRs technology have been presented in a significant number of review papers [26,38,[48][49][50][51][52][53][54][55]. According to the above-mentioned studies, the most important benefits of the AnMBRs application are high biomass concentration and enhanced biogas yield, effluent with excellent quality without suspended solids, small footprint, low sludge production, and high treatment capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The processes that involve membrane technology in the treatment of wastewaters are an alternative to the traditional methods such as sedimentation, oxidation and anaerobic treatments. In particular, the application of membrane bioreactors (MBRs) for treating wastewater has received increasing attention [17]. The membranes are devices with different compositions and pore sizes, which separate solids from a liquid stream.…”
Section: Introductionmentioning
confidence: 99%